Sport Utility Vehicles, Mini-Vans, and Light Trucks : An Overview of Fuel Economy and Emissions Standards. (U.S. Congressional Research., 2003)
Discusses the discrepancy between emissions and fuel economy standards for passenger cars and light trucks, how that discrepancy is changing, and legislative and regulatory activity related to these issues. Describes the roles of DOT and EPA in enforcing the Energy Policy and Conservation Act of 1975 and the Clean Air Act.